SYSTEMATIC LITERATURE REVIEW: CONTEXTUAL TEACHING AND LEARNING (CTL)-BASED MATHEMATICS LEARNING MODULE ON EXPONENTIAL MATERIAL IN CLASS X HIGH SCHOOL - Jaya, Patlan Putra; Elly, As; Yanto, Yufitri (Nindikayla Institute, 2024)
This study aims to conduct a literature review related to exponential learning using the Contextual Teaching and Learning (CTL) approach. The method used is Systematic Literature Review (SLR). The data used in this study is exponential learning information with the Contextual Teaching and Learning approach taken from selected articles. There were 10 articles used as data sources in this study with the following criteria: (1) the topic discussed was about exponential learning, (2) using the Contextual Teaching and Learning (CTL) approach, (3) the articles came from quality journals and were indexed by Sinta and Scopus.